POTENSI URBAN HERITAGE DALAM MENDUKUNG PENGEMBANGAN DESTINASI WISATA BUDAYA DI KAWASAN ISLAMIC CENTER TULANG BAWANG BARAT - Elvira, Dina Marisa; Mustofa, Asep Nurul Ajiid (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2023)
West Tulang Bawang Regency has 13 tourist destinations as stated in Regional Regulation Number 38 of 2016, 11 of which are cultural tourism, one of which is the West Tulang Bawang Islamic Center which is located in the Panaragan Jaya urban area which is the region's leading tourist attraction. Because it is a cultural tourism destination that has very strong cultural elements and is located in an urban area, it has great potential to be used as an Urban Heritage. This research aims to examine the potential of Urban Heritage in supporting the development of cultural tourism destinations in the Tulang Bawang Barat Islamic Center area. The method used is a combination with the squential exploratory model. The researcher develops the results of one method with other methods, with the first order using qualitative methods and the next method using quantitative. The results of this research are that the West Tulang Bawang Islamic Center Area has high potential as an Urban Heritage as seen from the 11 variables that have been determined, this potential supports the development of cultural tourism destinations in the West Tulang Bawang Islamic Center Area which is seen using the 4A Tourism components (Attraction, Accessibility, Amenities, and Ancillaries).